Serological evidence of virus infection in Eidolon helvum fruit bats: implications for bushmeat consumption in Nigeria - Cantoni, Diego; Mayora-Neto, Martin; Derveni, Mariliza; da Costa, Kelly; Del Rosario, Joanne; Ameh, Veronica O.; Sabeta, Claude T.; Auld, Bethany; Hamlet, Arran; Jones, Ian M.; Wright, Edward; Scott, Simon D.; et al. (Frontiers in Public Health, 2023)
Introduction The Eidolon helvum fruit bat is one of the most widely distributed fruit bats in Africa and known to be a reservoir for several pathogenic viruses that can cause disease in animals and humans. To assess the risk of zoonotic spillover, we conducted a serological survey of 304 serum samples from E. helvum bats that were captured for human consumption in Makurdi, Nigeria. Methods Using pseudotyped viruses, we screened 304 serum samples for neutralizing antibodies against viruses from the Coronaviridae, Filoviridae, Orthomyxoviridae and Paramyxoviridae families. Results We report the presence of neutralizing antibodies against henipavirus lineage GH-M74a virus (odds ratio 6.23; p < 0.001), Nipah virus (odds ratio 4.04; p = 0.00031), bat influenza H17N10 virus (odds ratio 7.25; p < 0.001) and no significant association with Ebola virus (odds ratio 0.56; p = 0.375) in this bat cohort. Conclusion The data suggest a potential risk of zoonotic spillover including the possible circulation of highly pathogenic viruses in E. helvum populations. These findings highlight the importance of maintaining sero-surveillance of E. helvum, and the necessity for further, more comprehensive investigations to monitor changes in virus prevalence, distribution over time, and across different geographic locations.